Soft landing of size selected clusters in rare gas matrices - Lau, J.T.; Ehrke, H.-U.; Achleitner, A.; Wurth, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Soft landing of mass selected clusters in rare gas matrices is a technique used to preserve mass selection in cluster deposition. To prevent fragmentation upon deposition, the substrate is covered with rare gas matrices to dissipate the cluster kinetic energy upon impact. Theoretical and experimental studies demonstrate the power of this technique. Besides STM, optical absorption, excitation, and fluorescence experiments, x-ray absorption at core levels can be used as a tool to study soft landing conditions, as will be shown here. X-ray absorption spectroscopy is also well suited to follow diffusion and agglomeration of clusters on surfaces via energy shifts in core level absorption.